PTH-113 Change In Awareness Of Gluten Related Disorders Amongst Chefs And The General Public In The United Kingdom: A 10 Year Follow-on Study. (9th June 2014) - Aziz, I; Karajeh, M; Zilkha, J; Tubman, E; Fowles, C; Sanders, DS
Abstract : Introduction: For individuals with gluten-related disorders (GRD) eating out has traditionally been difficult, and socially impacting, due to concern over the lack of public awareness regarding GRD and a gluten-free diet (GFD). However, the recent rise in media coverage highlighting these conditions may have altered knowledge amongst community members. Aims: To assess whether there has been a change in awareness of GRD, and a GFD, amongst the general public and chefs over a ten year period. Methods: A face-to-face questionnaire survey about coeliac disease (CD) and gluten sensitivity (GS) was performed on the general public and chefs based in Sheffield, United Kingdom. The assessment was first conducted in 2003 and repeated in 2013. Chefs were also asked about their workplace (takeaway or restaurant) and whether or not they had formal qualifications. Additional questions for the 2013 cohort included correct recognition of the cross-grain symbol to identify gluten-free products and whether they displayed a notice/sign for gluten-free products. Results: Public survey: 513 public members in year 2003 (mean age 49.2, 62% female) were compared to 575 public members in year 2013 (mean age 37.8, 57% female). Adjusting for age and sex, there was a significant rise in the awareness of GRD from the years 2003 to 2013; CD (44.2 to 74.4%, OR 3.94 [CI: 2.99–5.19]) and GS (58.2 to 89%, OR 7.09 [CI: 5–9.98]), p value < 0.0001. Chef Survey: 322 chefs in year 2003 (mean age 37.6, 15.2% female, qualified 51.2%, restaurant chefs 50%) were compared to 265 chefs in year 2013 (mean age 27.1, 38.1% female, qualified 93.2%, restaurant chefs 83%), p < 0.0001. Adjusting for age, sex, workplace and qualifications, there was a significant rise in the awareness of GRD from the years 2003 to 2013; CD (17.1 to 78.1%, OR 12.5 [CI: 7.9–19.6]) and GS (9.3 to 87.5%, OR 65.7 CI: [35.4–122]), p < 0.001. Whereas in 2003 the public were significantly more aware of GRD than chefs, by 2013 there was a similar prevalence of awareness in both groups. In addition, the correct recognition of the gluten-free symbol was 44% for the public and 40% for chefs (p 0.28). Furthermore, in the year 2013, 41% of restaurants and 27% of takeaways displayed selling gluten-free products (p 0.07). Conclusion: There has been a dramatic rise in both the public and chefs awareness of GRD. This suggests that individuals with GRD can take greater confidence discussing and ordering a GFD whilst eating out. Disclosure of Interest: None Declared.